Role of menaquinone biosynthesis genes in selenate reduction by Enterobacter cloacae SLD1a‐1 and Escherichia coli K12 - Jincai Ma; Donald Y. Kobayashi; Nathan Yee (Environmental Microbiology, 2009)
Summary In this study, we investigated the role of menaquinone biosynthesis genes in selenate reduction by Enterobacter cloacae SLD1a‐1 and Escherichia coli K12. A mini‐Tn5 transposon mutant of E. cloacae SLD1a‐1, designated as 4E6, was isolated that had lost the ability to reduce Se(VI) to Se(0). Genetic analysis of mutant strain 4E6 showed that the transposon was inserted within a menD gene among a menFDHBCE gene cluster that encodes for proteins required for menaquinone biosynthesis. A group of E. coli K12 strains with single mutations in the menF , menD , menC and menE genes were tested for loss of selenate reduction activity. The results showed that E. coli K12 carrying a deletion of either the menD , menC or menE gene was unable to reduce selenate. Complementation using wild‐type sequences of the E. cloacae SLD1a‐1 menFDHBCE sequence successfully restored the selenate reduction activity in mutant strain 4E6, and E. coli K12 menD and menE mutants. Selenate reduction activity in 4E6 was also restored by chemical complementation using the menaquinone precursor compound 1,4‐dihydroxy‐2‐nathphoic acid. The results of this work suggest that menaquinones are an important source of electrons for the selenate reductase, and are required for selenate reduction activity in E. cloacae SLD1a‐1 and E. coli K12.